THE CULTURAL LANDSCAPE OF KHATANGA IN THE XX – EARLY XXI CENTURIES: THE TRADITIONAL ECONOMY OF THE REGION ON THE EXAMPLE OF POPIGAI VILLAGE - Sannikova, Yana Mikhailovna (Agrarian History, 2022)
The article presents the topic of studying the traditional economy of Khatanga on the example of the village of Popigai. Based on the materials of field research, the following issues are considered: general information about the rural settlement of Khatanga and its traditional economy; features of the traditional economic occupations of the indigenous inhabitants of the village of Popigai; justification of the source base during the reconstruction of the state farm period of the life of Popigai residents. The topic under study is shown from the point of view of studying the cultural landscape of Khatanga as a separate research region.